The equation is f(x) = 4x^2 - 4.
You can find this by using an equation with parenthesis that equal each of the zeros.
f(x) = (x - 1)(x + 1)
Now, this equation will not give us the vertex that we're looking for. So, we must add a constant being multiplied to the front of it.
f(x) = c(x - 1)(x + 1)
Now we can find the constant by putting our vertex into the equation and solving.
f(x) = c(x - 1)(x + 1)
-4 = c(0 - 1)(0 + 1)
-4 = c(-1)(1)
-4 = -1c
c = 4
Now we put the c into the original equation and solve for standard form.
f(x) = 4(x - 1)(x + 1)
f(x) = 4(x^2 - 1)
f(x) = 4x^2 - 4